RSM-optimization of microwave-assisted extraction of R. laevigata polysaccharides with bioactivities - Gao, Pinyi; Shen, Xin; Guo, Yongdan; Jin, Mei; Yue, Dandan; Li, Danqi; Liu, Xuegui; Liu, Changfeng (Emirates Journal of Food and Agriculture, 2023)
Rosa laevigata Michx. is an edible traditional Chinese medicinal herb that possesses several health benefits. This study optimized the microwave-assisted extraction conditions of polysaccharides from Rosa laevigata fruits and investigated the antimicrobial potency and the antioxidant activity of Rosa laevigata polysaccharides. The microwave power, extraction time, the number of extraction, and the solvent-to-solid ratio were established using a three-factor, three-level Box-Behnken Design (BBD) and Response Surface Methodology (RSM) using screening experiments. Maximum polysaccharides yields were obtained when extraction was done for 18 min at a microwave power of 516 W and using a liquid-solid ratio of 54 mL/g. The polysaccharides yield was 20.37 % under the optimized conditions (predictive value for 20.40 %). This study also determined the antioxidant activity and the antibacterial potency of Rosa laevigata fruits to enhance their functional characterization and medicinal use. The antioxidant experiment showed that when the concentration was 5.0 mg/mL, polysaccharides had the strongest scavenging ability to DPPH free radicals and ABTS free radicals, and the scavenging rate was 83.06 % and 99.38 % respectively. Furthermore, the antibacterial experiment showed that the polysaccharides exhibited prominent inhibition activities, the MIC against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) at 3.13 mg/mL and 1.56 mg/mL, respectively. Keywords: Rosa laevigata Michx.; polysaccharides; microwave-assisted extraction; antibacterial activity; antioxidant activity